PROFIL MAHASISWA PENGGUNA JASA PELAYANAN PADA BALAI KESEHATAN UNIVERSITAS RIAU - Silvia Desvianti; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Health is one of the basic needs of society and the state is obliged to guarantee all OF theirpeoples, the government as the highest institution in charge of the health care must alsofulfill the obligations in the provision of health care facilities. This research aims toinvestigate the characteristics of college student who seek treatment in center healthservices of university of riau. This research was conducted in october, november anddecember 2013 by conducting interviews and direct observation in clinic university of riau.Furthermore, the data obtained from the field were analyzed descriptively. The resultsshowed that the characteristics of college student who seek treatment in health centerservices is dominated by respondents aged 20-22 years which is as much as 49.23% or 65respondents and dominated by female respondents ie 48 respondents or 69.23%.Characteristics of college student who seek treatment in center health services is dominatedby them who have a parent with an income of Rp. 2.000.000, - s / d Rp. 5.000.000, - permonth or middle economic status as much as 47.69%. The response of college students tohealth center services in university of Riau overall is good. Many as 43 respondents or66.15% of respondents who chose treatment because it is free give a good assessment. Thenin terms of the care of doctors and health workers also was considered quite good by therespondents.Keywords: Health Care, College Student, Health Center of University of Riau